2021
DOI: 10.3390/ijerph182211918
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the Occurrence of Physical Restraint Use in the Long-Term Care: A Scoping Review

Abstract: Physical restraints in the long-term care setting are still commonly used in several countries with a prevalence ranging from 6% to 85%. Trying to have a broad and extensive overlook on the physical restraints use in long-term care is important to design interventions to prevent and/or reduce their use. Therefore, the aim of this scoping review was to analyze the range of occurrence of physical restraint in nursing homes, long-term care facilities, and psychogeriatric units. Pubmed, CINAHL, Ovid PsycINFO- data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…42 A recent scoping review concluded that reported rates of restraint use decreased (nonsignificantly) over the last decade, which is to take into account when comparing our findings to results from earlier studies. 10 While the current study's data indicate a relatively low prevalence (11.1%) of restraint use, there is high variability between units (range: 0.0%-63.6%), and despite research findings suggesting that restraint-free nursing is an achievable goal in NHs, only 30.1% of our sample's units were providing such care. 43 We also investigated the relationship between the use of surveillance technologies and rates of physical restraint use.…”
Section: Discussioncontrasting
confidence: 88%
See 4 more Smart Citations
“…42 A recent scoping review concluded that reported rates of restraint use decreased (nonsignificantly) over the last decade, which is to take into account when comparing our findings to results from earlier studies. 10 While the current study's data indicate a relatively low prevalence (11.1%) of restraint use, there is high variability between units (range: 0.0%-63.6%), and despite research findings suggesting that restraint-free nursing is an achievable goal in NHs, only 30.1% of our sample's units were providing such care. 43 We also investigated the relationship between the use of surveillance technologies and rates of physical restraint use.…”
Section: Discussioncontrasting
confidence: 88%
“…Staff generally assess bedrails as less restrictive than belts, which partly explains the differences in prevalence between the two general types of restraints 42 . A recent scoping review concluded that reported rates of restraint use decreased (nonsignificantly) over the last decade, which is to take into account when comparing our findings to results from earlier studies 10 . While the current study's data indicate a relatively low prevalence (11.1%) of restraint use, there is high variability between units (range: 0.0%–63.6%), and despite research findings suggesting that restraint‐free nursing is an achievable goal in NHs, only 30.1% of our sample's units were providing such care 43 …”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations